Solvent Type Effect on Preparation of Ethyl Cellulose Microparticles - Muhaimin, Muhaimin; Chaerunisaa, Anis Yohana (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
The purpose of this study was to investigate effect of solvent type on solidification rate of ethylcellulose (EC) microparticles and particle size/distribution of emulsion droplets/hard microparticlesduring the solvent evaporation process using focused beam reflectance measurement (FBRM). ECmicroparticles were prepared by an O/W-solvent evaporation method using various solvents, includingdichloromethane, dichloromethane:methanol (1:1), ethyl acetate, and chloroform. The particle size/distribution of emulsion droplets/hard microparticles was monitored by FBRM. The morphology ofEC microparticles was characterized by scanning electron microscopy (SEM). The transformation ofemulsion droplets into solid microparticles for all solvents occured within the first 10-60 min. Thesquare weighted mean chord length of EC microparticles which were prepared using chloroform wassmallest value, but the chord counts was no the highest. The chord length distribution (CLD) measuredby FBRM showed that microparticles with a larger diameter give a wider CLD and a lower peaknumber of particles. SEM data shows that the morphology of microparticles was influenced by type ofsolvent. FBRM can be used to monitor the development of microparticle CLDs online and detect thetransformation of emulsion droplets into solid microparticles during the solvent evaporation process.The microparticle CLD and transformation processes are influenced by the type of solvent.